Presentation of Posner Schlossman Syndrome and Viral Uveitis - , Muhammad Safdar Iqbal, Muhammad Imran, Ashraf Ali Tayyab (Pakistan Journal of Ophthalmology, 2012)
Purpose: To discuss an interesting case in which treatment of Posner Schlossman syndrome lead to unmasking signs of viral Uveitis. Clinical management: A patients was brought to Nishtar hospital Multan for management of unilateral raised intra ocular pressure (IOP) being caused by anterior Uveitis. First examination revealed Posner Schlossman syndrome as a diagnosis of exclusion. After 48 hours of treatment features of viral uveitis appeared that lead to change the diagnosis.